Peningkatan Kemampuan Masyarakat dalam Optimalisasi Potensi Peternakan di Desa Cibodas, Kecamatan Pacet, Kabupaten Cianjur - Triwahyudi, Fajar Rizki; Kusuma, Bita Padma; Samih, Sulthan Falah; Ghimar, Migo Fannan; Febriyana, Aliyyah Zulfa; Nasution, Siti Noor Haliza; Pamungkas, Pandu Jati; Bashori, Sayid Akmal; Rahman, Dede Aulia (Jurnal Pusat Inovasi Masyarakat, 2025)
Desa Cibodas di Kabupaten Cianjur, Provinsi Jawa Barat, memiliki potensi besar dalam sektor peternakan, pertanian, dan pariwisata. Namun, desa ini juga menghadapi berbagai tantangan, seperti stunting, limbah peternakan, dan rendahnya efisiensi penggunaan sumber daya. Program pemberdayaan masyarakat di Desa Cibodas Village, Cianjur has great potential in the livestock, agriculture, and tourism sectors, however, this village also faces various challenges, such as stunting, livestock waste, and inefficient resource use. The community empowerment program in Cibodas Village aims to maximize local potential by utilizing livestock waste into products of economic value, such as organic fertilizer, mineral blocks, and silage, by providing training and knowledge to the community regarding the techniques for making these products. This activity uses the asset-based community development (ABCD) method, which focuses on identifying assets in the community that are considered able to support community empowerment activities. The community was also given guidance in the form of leaflets and demonstration videos to facilitate independent implementation. The community's response to this program has been very positive, and there has been a strong push to develop and utilize this innovation sustainably. Collaboration between parties, such as utilizing BUMDES land, is expected to support the sustainability of this program so that it can continue to grow and have a positive impact on community welfare and the local economy in Cibodas Village.